A GARCH Model to Understand the Volatility of the Electricity Spot Price in Brazil - da Silva Leite, André Luis; Andrade de Lima, Marcus Vinicius (International Journal of Energy Economics and Policy, 2023)
Electricity is sensitive to extreme price events and spot price volatility is an inherent characteristic of competitive electricity markets. The purpose of this article it to model the realized volatility of electricity spot price in Brazil. The Brazilian electricity industry presents unique characteristics and because of this price varies a lot in a short period. So, we developed a GARCH model using 862 weekly observations to understand the realized volatility in the four different market. We conclude that the spot price in Brazil presents high volatility that presents risk to agents. This high volatility is associated with institutional factors and the increase in the share of renewable energy in the electricity mix.